Comparing the Internet Usage of Pre-service Language Teachers With Teachers of Other Subjects: Distance Learning vs. On-Campus Learning - Mehmet Firat; Harun Serpil (Universidad Nacional de Colombia, 2017)
Teachers play a crucial role in helping individuals gain adequate Internet competency, which requires teachers themselves to be Internet-literate. The purpose of this study is to investigate the Internet use of the distance and on-campus pre-service teachers of language and other disciplines by multiple parameters. A total of 789 teacher candidates participated in this survey. The findings show that the candidate teachers in on-campus and distance-learning programs have an average level of Internet usage adequacy and that the younger candidate teachers and those in higher classes use the Internet more frequently. Pre-service foreign language teachers have been found to have a moderate level of Internet usage frequency, adequacy and technology ownership in comparison with the other preservice teacher groups.